2012
DOI: 10.1017/s0031182012001394
|View full text |Cite
|
Sign up to set email alerts
|

Congenital and oral transmission of American trypanosomiasis: an overview of physiopathogenic aspects

Abstract: Chagas disease or American trypanosomiasis is a pathology affecting about 8-11 million people in Mexico, Central America, and South America, more than 300 000 persons in the United States as well as an indeterminate number of people in other non-endemic countries such as USA, Spain, Canada and Switzerland. The aetiological agent is Trypanosoma cruzi, a protozoan transmitted by multiple routes; among them, congenital route emerges as one of the most important mechanisms of spreading Chagas disease worldwide eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 117 publications
(281 reference statements)
1
45
0
5
Order By: Relevance
“…T. cruzi has been classified into 6 discrete typing units (DTUs), TcI-TcVI, and, within TcI, into 2 genotypes (domestic TcI [TcI Dom ] and sylvatic TcI). In humans, this mechanism has been described in >1000 cases corresponding to 138 outbreaks, with a fatality rate of 8%-35% across Latin America [1,2]. In Colombia, between 1992 and 2009, 11 outbreaks were reported, with a lethality rate of 16.0% [3].…”
mentioning
confidence: 99%
“…T. cruzi has been classified into 6 discrete typing units (DTUs), TcI-TcVI, and, within TcI, into 2 genotypes (domestic TcI [TcI Dom ] and sylvatic TcI). In humans, this mechanism has been described in >1000 cases corresponding to 138 outbreaks, with a fatality rate of 8%-35% across Latin America [1,2]. In Colombia, between 1992 and 2009, 11 outbreaks were reported, with a lethality rate of 16.0% [3].…”
mentioning
confidence: 99%
“…As a consequence of active control in dwellings and their surroundings and the serological screening in blood banks, the transmission of the infection by vectorial and transfusional routes fell sharply in the last years (43). In this scenario, oral transmission appears as a route of emerging relevance (44)(45)(46)(47). Potential sources of food contamination are triatomine bugs or triatomine feces, raw meat from infected animals, and gland secretions of infected opossums (Didephis marsupalis) (44).…”
Section: Discussionmentioning
confidence: 99%
“…A population study of pregnant women from Argentina, Bolivia, Honduras, and Mexico, using umbilical cord blood samples, found that the rapid test on average sensitivity and specificity of 94.6 and 99,0%, respectively, suggesting the use of this test as alternative screening during childbirth 32 . Finally, some studies show that the sensitivity of rapid tests could be affected using whole blood samples, since sensitivity values increase when serum samples are analyzed 33,34 . Although there are limitations are identified in terms of reproducibility, in certain regions, rapid tests could be useful in special situations where there is no alternative, by allowing quick decisions.…”
Section: Section 2 Diagnosis In Pregnant Womenmentioning
confidence: 99%
“…Despite the potential benefits of the test, it must be considered that it requires a specialized infrastructure and that it is still in the process of standardization and validation in the different laboratories of the endemically countries 68,59 . Therefore, PCR is not recommended as a routine method for diagnosis 33,39 .…”
Section: Principles (Very Good Consensus) Level Of Evidence 2 (Degmentioning
confidence: 99%